2015
DOI: 10.1038/ejhg.2014.300
|View full text |Cite
|
Sign up to set email alerts
|

Rare variants in β-Amyloid precursor protein (APP) and Parkinson’s disease

Abstract: Many individuals with Parkinson's disease (PD) develop cognitive deficits, and a phenotypic and molecular overlap between neurodegenerative diseases exists. We investigated the contribution of rare variants in seven genes of known relevance to dementias (β-amyloid precursor protein (APP), PSEN1/2, MAPT (microtubule-associated protein tau), fused in sarcoma (FUS), granulin (GRN) and TAR DNA-binding protein 43 (TDP-43)) to PD and PD plus dementia (PD+D) in a discovery sample of 376 individuals with PD and follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…The patient had a family history of early-onset dementia and pathology examination of her brain revealed extensive Lewy body pathology (neocortical-type DLB) as well as severe Alzheimer pathology (Braak stage 6, CERAD score C) (table 2). The second APP mutation we detected, p.E599K, has been previously associated with parkinsonism (Schulte, et al, 2015) and likely constitutes a risk variant. In total, 2% of our cohort carried an APP missense mutation.…”
Section: Resultsmentioning
confidence: 64%
“…The patient had a family history of early-onset dementia and pathology examination of her brain revealed extensive Lewy body pathology (neocortical-type DLB) as well as severe Alzheimer pathology (Braak stage 6, CERAD score C) (table 2). The second APP mutation we detected, p.E599K, has been previously associated with parkinsonism (Schulte, et al, 2015) and likely constitutes a risk variant. In total, 2% of our cohort carried an APP missense mutation.…”
Section: Resultsmentioning
confidence: 64%
“…Ceruloplasmin (CP) enables iron export by converting Fe 2+ to Fe 3+ (Osaki et al, 1966), which is then bound to and removed by transferrin. Several rare variants of APP predispose individuals to PD (Schulte et al, 2015), and examination of several studies of familial AD indicate APP mutations are associated with parkinsonism (Edwards-Lee et al, 2005;Rosenberg et al, 2000), and LB formation (Halliday et al, 1997;Rosenberg et al, 2000). Similarly, several point mutations in the CP-encoding gene are significantly associated with PD (Hochstrasser et al, 2004), and parkinsonism (Kohno et al, 2000;Miyajima et al, 2003), indicating that CP-mediated iron homeostasis mechanisms are also likely involved in PD pathogenesis.…”
Section: Ferroptosis-a Possible Cell Death Pathway In Pdmentioning
confidence: 99%
“…Evidence supporting pathological involvement of ferroptosis in humans (blue circles), and evidence suggesting pharmacological modulators of ferroptosis could be beneficial in PD (purple circles). Blue: (1) transferrin (Tf)-mutations increase susceptibility (Borie et al, 2002;Rhodes et al, 2014); (2) ceruloplasmin (CP)-mutations increase susceptibility (Rhodes et al, 2014); (3) amyloid precursor protein (APP)-mutations increase susceptibility, expression levels reduced in PD (Ayton et al, 2015b;Schulte et al, 2015); (4) reduced-glutathione-nigral depletion (Jenner et al, 1992); (5) ferrous iron (Fe(II))-nigral elevation ; Dexter et al, 1991;Dexter et al, 1989b;Good et al, 1992;Hirsch et al, 1991;Lei et al, 2012;Sofic et al, 1988); (6) lipid peroxidation-nigral elevation (Dexter et al, 1989a, Dexter et al, 1986. Purple: (1) deferiprone (DFP)-motor improvement in phase II clinical trial.…”
Section: Figure Legendmentioning
confidence: 99%
“…In the amyloidogenic path way cleavage by β-secretase (BACE) and γ-secretase releases amyloid-β42 (Aβ42), which plays an important role in early pathological events in early-onset familial AD and sporadic age-related AD (8,10). Moreover, previous studies have shown that other age-related diseases, such as Parkinson's disease and age-related macular degeneration, are accompanied by high levels of expression of APP (11)(12)(13)(14). However, the biological activity of APP in SK is unknown.…”
mentioning
confidence: 99%